A review of nonlinear hysteresis modeling and control of piezoelectric actuators - Jinqiang Gan; Xianmin Zhang (AIP Advances, 2019)
Piezoelectric actuators are gradually playing an important role in precision positioning applications due to their extremely fine resolution, fast responses, and large actuating forces. However, the existence of hysteresis behaviors makes a big influence on their positioning accuracies. To get high positioning accuracies, hysteresis modeling and control of piezoelectric actuators are meaningful and necessary. This paper reviews different models and control approaches of piezoelectric actuators. Novel categories of both hysteresis models and control approaches are presented. Furthermore, comparisons of different hysteresis models reveal that rate-dependent differential-based modeling is the future research focus. Comparisons of control approaches of piezoelectric actuators are presented and feedforward-feedback control and feedback control are the emphasis in the future.